Bacterial pathogens causing UTI and their antibiotic sensitivity pattern: a study from a tertiary care hospital from South India - Dr. P. Sneka; Dr. V. Mangayarkarasi (Tropical Journal of Pathology and Microbiology, 2019)
Objectives: This study was conducted to find out the prevalence of pathogens causing UTI and their antibiotic sensitivity pattern. Materials and Methods: A Prospective study was carried out in the department of Microbiology for one year period from January to December 2018collaboratingwith the various clinical departments to determine the spectrum of organisms causing urinary tract infections and to determine their antibiotic susceptibility profile. Results: Among the 8303 samples tested significant bacteriuria was observed in 33.14%. The incidence of UTI was more common in females and in the age group of 31-40 years. In this study, 1931 (70.6%) gram negative bacilli and 756 (27.4%) gram positive cocci were isolated, among which E.coli (61.2%) was the commonest followed by Klebsiella (18.90%), Pseudomonas (8.02 %), Acinetobacter (4.4%), Proteus (3.7%) and Citrobacter (3.72%). Among the gram positive organisms Entetrococcus (87.4%) was the highest followed by Coagulase negative staphylococcusaureus (CONS) (7.9%) and Staphlococcus aureus (4.6%). Candida was isolated in 65cases (2.3%). Imipenem (100%) was the most susceptible antibiotic for Enterobacteriaciae followed by levofloxacin (83%) and Amikacin (82%). For the gram positive organisms Vancomycin (100%) and Linezolid (100%) was the most susceptible antibiotic followed by Nitrofurantoin (80%) and Gentamycin (60%). For both the gram positive and the gram negative organisms Nalidicacid, Norfloxacin, Cotrimoxazole and ampicillin were highly resistant and showed less than 30%sensitivity. Conclusion: Knowledge of the pattern of organisms causing UTI and their sensitivity pattern is important in choosing empirical drugs in the treatment of UTI.